Staatssicherheit und Wirtschaftskrise: Warnungen des MfS vor dem ökonomischen Niedergang der DDR in den 1980er Jahren - Malycha, Andreas (2014)
Abstract: "Internal reports and information by the MfS more or less clearly addressed the actual economic situation in the GDR, also naming some of the causes. The secret analyses Mielke was presented with by the MfS Hauptabteilung (Main Department) XVIII uncovered some of the functional flaws of the planned economy, naming Günther Mittag as being responsible for a misguided economic policy. However, the MfS by its analyses was not able to offer any conceptual or personal alternative to the SED's economic course which could have been enforced under the prevailing political conditions." (author's abstract)